Clinical relevance of blood urea nitrogen to serum albumin ratio for predicting bacteremia in very young children with febrile urinary tract infection - Hyesun Hyun; Yeonhee Lee; Na Yoon Kang; Jin-Soon Suh (The Korean Society of Nephrology, 2024)
Background Urinary tract infections (UTIs) are one of the most common bacterial infections in febrile children and a common cause of hospitalization, especially in very young children. We examined the clinical characteristics and predictive factors of concomitant bacteremia in pediatric patients with febrile UTI aged ≤24 months. Methods This retrospective multicenter study reviewed medical data from 2,141 patients from three centers from January 2000 to December 2019. Enrolled cases were classified into the bacteremic UTI and non-bacteremic UTI groups according to the presence of blood culture pathogens. Results Among 2,141 patients with febrile UTI, 40 (1.9%) had concomitant bacteremia. All patients in the bacterial group were aged ≤6 months. Multivariate analysis revealed that younger age, lower blood lymphocyte counts and serum albumin levels, higher C-reactive protein (CRP) levels, blood urea nitrogen (BUN) levels, and BUN/serum albumin ratio were independent risk factors of concomitant bacteremia. The area under the receiver-operating characteristic curves predicting bacteremia were 0.668 for CRP, 0.673 for lymphocytes, and 0.759 for the BUN/albumin ratio. Conclusion The present study identified the BUN/albumin ratio and lower blood lymphocyte counts as novel predictive factors for bacteremia in young infants with febrile UTI in addition to the previously identified factors of younger age and higher CRP levels. Our findings could help to identify patients at high risk of bacteremia and benefit decision-making in the management of infants with febrile UTI.